Mobile learning languages, literacies and cultures - Pegrum, Mark.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explores the use of mobile devices for teaching and learning language and literacies, investigating the ways in which these technologies open up new educational possibilities. Pegrum builds up a rich picture of contemporary mobile learning and outlines of likely future developments.
Keywords: Education; Linguistics; English language; Educational technology; Language and education; Language and languages -- Study and teaching; Education; Technology and Digital Education; Language Education; Language Teaching; Educational Technology; Linguistics, general; English